HUBUNGAN USIA IBU DAN PARITAS DENGAN KEJADIAN ABORTUS DI KLINIK UTAMA PANASEA - Siti Mas'udah; Tutik Ekasari; Homsiatur Rohmatin (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Abortion is an important problem in public health because it affects maternal morbidity and mortality, the aim of this research is to analyze the correlation between maternal age and parity with the incidence of abortion. The research used was Correlation Analytical using a Cross Sectional approach with a population of 40 respondents and a sample of 36 respondents using a simple random sampling technique. By giving questionnaires to USG poly patients in April – May 2023 using univariate analysis and bivariate analysis to test and explain the correlation between the dependent variable and the independent variables using the chi-square test. The results of this study show that the Chi Square test was carried out with a safety level of α = 0.05 and obtained a value of p = 0.009 which is smaller than alpha (0.05). meaning that there is a relationship between maternal age and abortion and it is known that maternal parity with abortion at the Panasea main clinic using the Chi Square test is carried out with a safety level of α = 0.05 and the value of p = 0.066 is greater than alpha (0.05). it mean there is no correlation between parity and abortion. Age and parity are not the only factors that cause abortion because there are other factors that cause abortion, such as nutritional status, anemia, work and other diseases, so it is recommended that midwives improve their services, especially in the first trimester.